Implementing health promotion tools in Australian Indigenous primary health care. (26th July 2016) - Percival, Nikki A; McCalman, Janya; Armit, Christine; O'Donoghue, Lynette; Bainbridge, Roxanne; Rowley, Kevin; Doyle, Joyce; Tsey, Komla
Abstract: Background: In Australia, significant resources have been invested in producing health promotion best practice guidelines, frameworks and tools (herein referred to as health promotion tools) as a strategy to improve Indigenous health promotion programmes. Yet, there has been very little rigorous implementation research about whether or how health promotion tools are implemented. This paper theorizes the complex processes of health promotion tool implementation in Indigenous comprehensive primary healthcare services. Methods: Data were derived from published and grey literature about the development and the implementation of four Indigenous health promotion tools. Tools were theoretically sampled to account for the key implementation types described in the literature. Data were analysed using the grounded-theory methods of coding and constant comparison with construct a theoretical implementation model. Results: An Indigenous Health Promotion Tool Implementation Model was developed. Implementation is a social process, whereby researchers, practitioners and community members collectively interacted in creating culturally responsive health promotion to the common purpose of facilitating empowerment. The implementation of health promotion tools was influenced by the presence of change agents; a commitment to reciprocity and organizational governance and resourcing. Conclusion: The Indigenous Health Promotion Tool Implementation Model assists in explaining how health promotion tools are implemented and the conditions that influence these actions. Rather than simply developing more health promotion tools, our study suggests that continuous investment in developing conditions that support empowering implementation processes are required to maximize the beneficial impacts and effectiveness of health promotion tools.